Tofacitinib Suppresses Natural Killer Cells In Vitro and In Vivo: Implications for Amyotrophic Lateral Sclerosis - Figueroa-Romero, Claudia; Monteagudo, Alina; Murdock, Benjamin J.; Famie, Joshua P.; Webber-Davis, Ian F.; Piecuch, Caroline E.; Teener, Samuel J.; Pacut, Crystal; Goutman, Stephen A.; Feldman, Eva L. (Frontiers in Immunology, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal and incurable neurodegenerative disease with few therapeutic options. However, the immune system, including natural killer (NK) cells, is linked to ALS progression and may constitute a viable therapeutic ALS target. Tofacitinib is an FDA-approved immunomodulating small molecule which suppresses immune cell function by blocking proinflammatory cytokine signaling. This includes the cytokine IL-15 which is the primary cytokine associated with NK cell function and proliferation. However, the impact of tofacitinib on NK activation and cytotoxicity has not been thoroughly investigated, particularly in ALS. We therefore tested the ability of tofacitinib to suppress cytotoxicity and cytokine production in an NK cell line and in primary NK cells derived from control and ALS participants. We also investigated whether tofacitinib protected ALS neurons from NK cell cytotoxicity. Finally, we conducted a comprehensive pharmacokinetic study of tofacitinib in mice and tested the feasibility of administration formulated in chow. Success was assessed through the impact of tofacitinib on peripheral NK cell levels in mice. We found tofacitinib suppressed IL-15-induced activation as measured by STAT1 phosphorylation, cytotoxicity, and pro-inflammatory gene expression, and pro-inflammatory cytokine secretion in both an NK cell line and primary NK cells. Furthermore, tofacitinib protected ALS neurons from NK cell-mediated cytotoxicity. In mice, we found tofacitinib bioavailability was 37% in both male and female mice; using these data we formulated mouse containing low and high doses of tofacitinib and found that the drug suppressed peripheral NK cell levels in a dose-dependent manner. These results demonstrate that tofacitinib can suppress NK cell function and may be a viable therapeutic strategy for ALS.